2016
DOI: 10.3171/2015.11.jns151465
|View full text |Cite
|
Sign up to set email alerts
|

Endosphenoidal coil for intraoperative magnetic resonance imaging of the pituitary gland during transsphenoidal surgery

Abstract: OBJECTIVE Pituitary MR imaging fails to detect over 50% of microadenomas in Cushing’s disease and nearly 80% of cases of dural microinvasion. Surface coils can generate exceptionally high-resolution images of the immediately adjacent tissues. To improve imaging of the pituitary gland, a receive-only surface coil that can be placed within the sphenoid sinus (the endosphenoidal coil [ESC]) during transsphenoidal surgery (TSS) was developed and assessed. METHODS Five cadaver heads were used for preclinical test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…69 We tested the ESC in cadavers using an existing iMRI system (1.5 T, Achieva, Phillips Healthcare) and demonstrated that SNR values 5 – 12 (mean 10.9 ± 1.6) times those achievable with conventional surface coils. We also showed that ultra-high resolution imaging of the sella (voxel size = 0.15 × 0.15 × 0.3 mm 3 ) could be achieved within a reasonable image acquisition time (~ 6 minutes).…”
Section: Imri For Tssmentioning
confidence: 99%
“…69 We tested the ESC in cadavers using an existing iMRI system (1.5 T, Achieva, Phillips Healthcare) and demonstrated that SNR values 5 – 12 (mean 10.9 ± 1.6) times those achievable with conventional surface coils. We also showed that ultra-high resolution imaging of the sella (voxel size = 0.15 × 0.15 × 0.3 mm 3 ) could be achieved within a reasonable image acquisition time (~ 6 minutes).…”
Section: Imri For Tssmentioning
confidence: 99%
“…По данным обзора P. S. Jones и B. Swearingen, обобщивших результаты наиболее крупных исследований и собственные данные, применение МРТ во время операции повышает вероятность радикальной резекции и позволяет прицельно контролировать декомпрессию ключевых функциональных анатомических структур [76]. Использование эндосфеноидальной приемной катушки может существенно улучшить качество интраоперационной визуализации структур селлярной области, в том числе межкавернозных синусов [77].…”
Section: Russian Journal Of Neurosurgeryunclassified
“…One example in clinical use, the endorectal coil designed for prostate imaging [12], has had limited use due to patient discomfort related to the relatively large diameter of the endorectal component. Chittiboina et al [13] adopted the endorectal prostate coil for pituitary imaging. The study demonstrated a potential 10-fold increase in SNR by positioning the coil apparatus within the sphenoid sinus via a sublabial approach in a cadaver [13].…”
Section: Introductionmentioning
confidence: 99%
“…Chittiboina et al [13] adopted the endorectal prostate coil for pituitary imaging. The study demonstrated a potential 10-fold increase in SNR by positioning the coil apparatus within the sphenoid sinus via a sublabial approach in a cadaver [13]. However, the design included a potential concern that the coil is needed to be positioned blindly, given the complete obstruction of the surgical corridor by the probe.…”
Section: Introductionmentioning
confidence: 99%